CIDADES INTELIGENTES, MAIS TECNOLOGIA, MAIS OPORTUNIDADES - Oliveira, Naiara Eduarda; Luiz Nery da Silva, Rogério (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
This research has as its theme the Smart cities and by clipping the integration of information and communication technologies to provide greater efficiency of services and meet the needs of society, through its association to city systems. The research is justified by the wide range of sectors beneficiaries, such as government services, public safety, the urban mobility, the supply of energy, water and very opportunely the Waste Management. The research problem is to identify obstacles to which this process takes place more broadly, with so many cities still following on the fringes of this possibility. It is crucial to identify the support systems that characterize a city as smart, focused on planning, managing, and operationalize the actions of the public power in the city. the cities program sustainable development (PCS) consists of an urban sustainability agenda that aggregates the political, economic, environmental, social, and cultural dimensions in planning municipal urban. The intention is to sensitize and mobilize the municipalities to get involved through effective public policies to structure their systems.